2003
DOI: 10.1136/sti.79.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Female genital mutilation in the Sudan: survey of the attitude of Khartoum university students towards this practice

Abstract: Background: Female genital mutilation (FGM) or female circumcision is the removal of variable amounts of tissue from the female external genitalia. It is practised all over the world on very young girls. This study was conducted in Sudan where FGM is a criminal offence and not a religious dictate. We assessed the knowledge, attitudes, and perceptions of this practice among Khartoum university students and compared the differences between male and female student responses. Methods: An anonymised detailed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 8 publications
4
28
0
Order By: Relevance
“…In Sudan there is lack of support by religion and law to fight the FGM practice and we believe that the confusing role of the religion and ambiguous law are essential reasons for the continuation of the FGM practice. Thus involvement of religion persons and educationalists together with a clear cut law to punish the circumcisers will decrease its prevalence in this country [6]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Sudan there is lack of support by religion and law to fight the FGM practice and we believe that the confusing role of the religion and ambiguous law are essential reasons for the continuation of the FGM practice. Thus involvement of religion persons and educationalists together with a clear cut law to punish the circumcisers will decrease its prevalence in this country [6]. …”
Section: Discussionmentioning
confidence: 99%
“…Female genital mutilation in Sudan is performed irrespective of females’ social or religious groups and the law in the Sudan forbids the practice of FGM. In the present there is no governmental or social attempt to eliminate the practice and the uncircumcised girl looks odd and unmarriageable [5,6]. Thus the current study is directed to assess knowledge and attitudes of the midwives towards FGM and it is expected to provide the health planners with fundamental data for the development of strategies that might reduce this practice.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they often referred to the hadiths to justify the acceptance of the practice by Islam (Hadiths: stories handed down orally and later recorded, related to the actions and sayings of the Prophet Muhammad, which represent, after the Qur'an, the second source of Islamic teachings) (Scolart, 2004). The perception of the practice as an Islamic requirement has been reported among men in Sudan (Almroth et al, 2001;Herieka and Dhar, 2003;Berggren et al, 2006) and Gambia (Kaplan et al, 2013). Interviews with 222 male university students in Khartoum, Sudan, found that only 14 percent supported the practice.…”
Section: Resultsmentioning
confidence: 92%
“…Interviews with 222 male university students in Khartoum, Sudan, found that only 14 percent supported the practice. Among these, 77.4 percent believed it is dictated by Islam (Herieka and Dhar, 2003). Berggren et al found that religion was invoked by men as an argument both for and against the practice and many of them claimed that the close link between religion, culture and tradition is an obstacle to changing the tradition (Berggren et al, 2006): those men who wanted their daughter to undergo FGM/C, preferred clitoridectomy (often called sunna) with a belief that it is required by Islam.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation